PM2.5 Induced the Expression of Fibrogenic Mediators via HMGB1-RAGE Signaling in Human Airway Epithelial Cells. (28th January 2018) - Zou, Weifeng; He, Fang; Liu, Sha; Pu, Jinding; Hu, Jinxing; Sheng, Qing; Zhu, Tao; Zhu, Tianhua; Li, Bing; Ran, Pixin
Abstract : Background . The aim of the present study was to test whether fine particulate matter (PM2.5) induces the expression of platelet-derived growth factor-AB (PDGF-AB), PDGF-BB, and transforming growth factor- β 1 (TGF- β 1) in human bronchial epithelial cells (HBECs) in vitro via high-mobility group box 1 (HMGB1) receptor for advanced glycation end products (RAGE) signaling. Methods . Sprague-Dawley rats were exposed to motor vehicle exhaust (MVE) or clean air. HBECs were either transfected with a small interfering RNA (siRNA) targeting HMGB1 or incubated with anti-RAGE antibodies and subsequently stimulated with PM2.5. Results . The expression of HMGB1 and RAGE was elevated in MVE-treated rats compared with untreated rats, and PM2.5 increased the secretion of HMGB1 and upregulated RAGE expression and the translocation of nuclear factor κB (NF-κB) into the nucleus of HBECs. This activation was accompanied by an increase in the expression of PDGF-AB, PDGF-BB, and TGF- β 1. The HMGB1 siRNA prevented these effects. Anti-RAGE antibodies attenuated the activation of NF- κ B and decreased the secretion of TGF- β 1, PDGF-AB, and PDGF-BB from HBECs. Conclusion . PM2.5 induces the expression of TGF- β 1, PDGF-AB, and PDGF-BB in vitro via HMGB1-RAGE signaling, suggesting that this pathway may contribute to the airway remodeling observed in patients with COPD.